Different Uptake of 68Ga-FAPI and 18F-FDG in Lymphadenopathy Caused by Angioimmunoblastic T-Cell Lymphoma in a Patient with Colon Cancer - Meiqi Wu; Qingqing Pan; Yaping Luo (Diagnostics, 2022)
An 82-year-old man with a history of colon cancer was found with multiple lymphadenopathies and a pulmonary mass. Fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) detected generalized hypermetabolic lymph nodes and an FDG-avid pulmonary mass. PET/CT with 68Ga-labeled fibroblast activation protein inhibitor (FAPI) revealed intense uptake in the lung mass, consistent with metastatic disease from colon cancer. However, the lymphadenopathies were not avid for 68Ga-FAPI, suggesting a different etiology. The biopsy of a cervical node confirmed angioimmunoblastic T-cell lymphoma. The case showcased the potential of 68Ga-FAPI in differentiation of solid tumor and hematological disease due to different histopathologic nature of stromal fibrosis.